EXPERIMENTAL STUDIES OF PIVOTALLY CONNECTED CAR PLATFORM FOR LARGE-CAPACITY CONTAINERS MODEL 13-1839 - Bubnov, V. M.; Myamlin, S. V.; Hurzhy, N. L. (Science and Transport Progress, 2009)
The work is devoted to experimental researches of pre-production model of swing-joint platform. An amount and order of conducting the preliminary tests, combinations of the test loadings are considered. The locations of setting the sensors as well as the locations of registered maximum equivalent tensions are selected. The convergence of results of tests with the results of theoretical calculations is analyzed.